A PROSPECTIVE STUDY ON MANAGEMENT OF CARDIOGENIC SHOCK WITH PERCUTANEOUS CORONARY INTERVENTION - JAN, MT; KHAN, MA; NOMAN, M; ULLAH, H; ALAM, K; RIAZ, M (Biological and Clinical Sciences Research Journal, 2024)
Cardiogenic shock following acute myocardial infarction (AMI) is a critical condition with high mortality rates. Percutaneous coronary intervention (PCI) has emerged as a key intervention, but the outcomes and associated risk factors, including comorbidities such as hypertension, diabetes, and smoking, remain essential to understand for optimizing treatment and improving prognosis. Objective: To evaluate outcomes and identify risk factors in patients with cardiogenic shock secondary to acute myocardial infarction managed with percutaneous coronary intervention. Methods: A prospective observational study was conducted at a tertiary care hospital involving 70 patients aged 60 years and above who presented with cardiogenic shock due to AMI within 24 hours of symptom onset. Data were collected on demographics, clinical indicators of shock severity, and mechanical complications, including pump failure, papillary muscle rupture, ventricular septal rupture (VSR), and free wall rupture. The incidence of comorbidities, such as hypertension, diabetes, and smoking status, was documented. Mortality and recovery patterns were assessed during hospitalization and post-discharge. Statistical analysis was performed to examine associations between comorbidities and adverse outcomes. Results: The mean age of the cohort was 68.8 ± 4.5 years, with a male predominance of 57.1%. Key complications included pump failure in 31.4%, papillary muscle rupture in 11.4%, papillary muscle dysfunction in 34.3%, VSR in 7.1%, and free wall rupture in 4.3% of patients. Overall mortality was 12.9%. Hypertension was present in 67.1% of patients, diabetes in 61.4%, and smoking in 21.4%, all of which correlated with higher complication rates and adverse outcomes. Conclusion: Early PCI management in patients with cardiogenic shock secondary to AMI is associated with favorable survival rates. However, comorbidities such as hypertension and diabetes significantly increase complication rates. These findings underscore the importance of timely intervention and risk-targeted management to improve survival outcomes in high-risk patients.